Practical handbook on image processing for scientific and technical applications - Jähne, Bernd (CRC Press, 2004)
Image processing is fast becoming a valuable tool for analyzing multidimensional data in all areas of natural science. Since the publication of the best-selling first edition of this handbook, the field of image processing has matured in many of its aspects from ad hoc, empirical approaches to a sound science based on established mathematical and physical principles.